2010
DOI: 10.1111/j.1365-4632.2010.04576.x
|View full text |Cite
|
Sign up to set email alerts
|

Could azathioprine be considered as a therapeutic alternative in the treatment of alopecia areata? A pilot study

Abstract: Alopecia areata is an autoimmune disease resulting in partial or total nonscarring hair loss and the treatment of severe alopecia areata is difficult. The aim of this study was to evaluate the efficacy and safety of azathioprine as a systemic monotherapy for moderate to severe alopecia areata. A total of 20 patients [14 men (70%) and six women (30%)] with minimum 6 months history of alopecia areata were included. The extent of scalp hair regrowth during and after the completion of the 6 months treatment was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 20 publications
5
48
1
2
Order By: Relevance
“…reported important hair regrowth in 20 patients with alopecia areata with a dose of 2 mg/kg in a lapse of 6 months [81]. However, more studies are needed to support these results.…”
Section: Azathioprinementioning
confidence: 53%
“…reported important hair regrowth in 20 patients with alopecia areata with a dose of 2 mg/kg in a lapse of 6 months [81]. However, more studies are needed to support these results.…”
Section: Azathioprinementioning
confidence: 53%
“…15 Furthermore, although none of them were taking immunomodulators at the time of alopecia, 2 had subsequent regrowth of hair after treatment with azathioprine. 15,16 Despite the fact that AA is not a recognized extraintestinal manifestation of IBD, 23 these cases, all of whom had AA, suggest that there may be an association between the 2 conditions. Supporting this, a case series assessing autoimmune disorders associated with IBD found an increased prevalence of AA in patients with UC, but not CD, compared with controls.…”
Section: Alopecia Associated With Ibdmentioning
confidence: 89%
“…Two patients with CD had complete reversal of AA within 6 months of starting azathioprine. 15,16 Methotrexate Like thiopurines, methotrexate targets rapidly dividing cells and as a result causes death of hair follicle cells and subsequent hair loss. Alopecia is occasionally reported as a side effect of methotrexate in IBD, although usually not requiring drug withdrawal.…”
Section: -Aminosalicylic Acid and Sulfasalazinementioning
confidence: 99%
“…An open-label uncontrolled study and a recently published prospective study suggested that AZT Might be an alternative [49,50].…”
Section: Azathioprinementioning
confidence: 99%